Polska polityka rolna w świetle ochrony środowiska przyrodniczego - Kociszewski, Karol (Polish Agricultural Policy in the Context of Environment Protection, 2006)
The paper deals with strategic documents of agricultural and ecological policies in the context of solutions concerning environment protection in agriculture. Problems of environment pollution arising from agriculture implicate proper policy as far as both protection of the Baltic Sea and requirements connected with accession to the European Union are concerned. The study purpose is the appraisal of so far implemented environment protection programs within agricultural policy. The appraisal was carried out in the context of leading in the most important instruments – agri-environmental measures and delimitation of areas sensitive to nitrogens from agriculture. The documents include realization plans but they are too general and have some deficiencies. In some cases they are not coordinated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 167-182